2012
DOI: 10.3141/2299-07
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Pedestrian Traffic Signals by Pedestrians with Varying Levels of Vision

Abstract: This study evaluates the usability of pedestrian signals by persons with varying visual acuities under different conditions of symbol size, crossing length and type of background behind the pedestrian signal. While viewing photographs presented on a computer monitor under unimpaired viewing conditions (approx. 20/20 visual acuity) and under simulated visual impairment (approx. acuities of 20/100 and 20/300), participants attempted to determine the pedestrian phase (Walk or Don’t Walk) and to report the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Some of what is known about the relationship between CVL and its effects on task performance comes from studies that have simulated vision impairment. Commonly used simulations include optical defocus (refractive blur),1217 diffusive filters,1722 and image blur (though image processing) 15,16,2024. These may resemble the “initial stages of sudden onset, acquired visual loss”18 due to cataract, keratoconus, corneal scarring, or uncorrected refractive error in that their primary effect is a uniform reduction in image resolution across the visual field.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Some of what is known about the relationship between CVL and its effects on task performance comes from studies that have simulated vision impairment. Commonly used simulations include optical defocus (refractive blur),1217 diffusive filters,1722 and image blur (though image processing) 15,16,2024. These may resemble the “initial stages of sudden onset, acquired visual loss”18 due to cataract, keratoconus, corneal scarring, or uncorrected refractive error in that their primary effect is a uniform reduction in image resolution across the visual field.…”
mentioning
confidence: 99%
“…These may resemble the “initial stages of sudden onset, acquired visual loss”18 due to cataract, keratoconus, corneal scarring, or uncorrected refractive error in that their primary effect is a uniform reduction in image resolution across the visual field. Such simulations have been used to study reading,13,14,19,25 pedestrian mobility,1517 postural stability,22 gaze perception,16 eye–hand coordination,24 and driving 17. In addition, “visual impairment simulators,” which can be found at trade shows or in the laboratory,26,27 have been used to study way-finding,28 pharmacy education,27,29 and the impact on the empathy of medical residents 30…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the benefits, vision impaired pedestrians face a particular challenge when using these signals. Scott et al (2012) found that people with vision acuity issues successfully identify phase changes with 87 percent accuracy, but they have a significantly more difficult time recognizing the countdown display.…”
Section: The Color-coded Pedestrian Systemmentioning
confidence: 97%